Η πανελλήνιος οργάνωση: Η "άγνωστη" φάση του Ελληνικού επαναστατικού αγώνα στην ευρωπαϊκή Τουρκία, 1908-1909 - Ψηλός, Χριστόφορος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2008)
Hellenic underground revolutionary activity in European Turkey, after the successful Young Turk coup in Macedonia in July 1908, has not become the object of any systematic historical research so far, with the notable exception of Professor Gounaris’ study (1984). The present article shall attempt to fill in that void. Outlining the organizational structure, function and activity of the Πανελλήνιος ’Οργάνωση (Panhellenic Organization, Π.Ο.), the basic Greek revolutionary apparatus which had been active from summer 1908 to autumn 1909 in Turkey-in-Europe, has been neither the chief nor the sole intent of the article. The main purpose of this study is to focus and elaborate on colonel Danglis’ (head of the Π.Ο.) operational plan for the solidification, development and advancement of the Organization. Colonel Danglis had embraced the belief that the implementation of the Π.Ο. program depended upon its integration into Greek state machinery, and particularly the Foreign Office. The military leader of the Π.Ο. argued that the Π.Ο. should initially built an effective revolutionary network in Ottoman territory. After a reasonable period of time the Π.Ο. could evolve into a powerful tool that would undertake to promote the economic interests and political emancipation of the Greek populations living under Ottoman rule. This study was based on manuscript archival sources, drawn mainly from the Historical Archive of the Hellenic Ministry of Foreign Affairs, and selected secondary sources.